Inequality of educational opportunity in India: Changes over time and across states - M. Niaz Asadullah; Gaston Yalonetzky (Institute for the Study of Labor (IZA), 2010)
This paper documents the extent of inequality of educational opportunity in India spanning the period 1983-2004 using National Sample Survey (NSS) data. We build on recent developments in the literature that has operationalized concepts in the inequality of opportunity theory (including Roemer's) and construct three indices of inequality of educational opportunity using data on an adult sample. Irrespective of the index used, the state of Kerala stands out as the least unequal in terms of educational opportunities. However, even after excluding Kerala, significant inter-state divergence remains amongst the remaining states. Transition matrix analysis confirms substantial inter-temporal mobility in inequality of opportunity across Indian states. Rajasthan and Gujarat in the West and Uttar Pradesh and Bihar in the Centre experienced large-scale fall in the ranking of inequality of opportunities. However, despite being poor, Eastern states of West Bengal and Orissa made significant progress in reducing inequality of opportunity. At a region level, Southern, Northeastern and Eastern regions on average experienced upward mobility (i.e. decline in inequality of opportunity) whilst the Central region experienced downward mobility. We conclude by examining the link between progress towards equality of opportunity and poverty reduction, growth and a selection of pro-poor policies.
Keywords: D63; O53; 330; schooling mobility; dissimilarity index; Gini of opportunity index; overlap index; Bildungschancen; Soziale Ungleichheit; Sozialer Indikator; Teilstaat; Indien